2014
DOI: 10.1186/s12888-014-0218-7
|View full text |Cite
|
Sign up to set email alerts
|

Rotating night shifts too quickly may cause anxiety and decreased attentional performance, and impact prolactin levels during the subsequent day: a case control study

Abstract: BackgroundWe investigated circadian changes and effects on mood, sleep-related hormones and cognitive performance when nurses worked consecutive night shifts in a rapidly rotating shift system. Daytime cognitive function, sleep propensity and sleep-related hormones (growth hormone, cortisol, prolactin, thyrotropin) were compared after participants worked two and four consecutive night shifts.MethodsTwenty-three off-duty nurses, 20 nurses working two consecutive night shifts and 16 nurses working four consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
(29 reference statements)
1
19
0
5
Order By: Relevance
“…A difference in shift schedules (permanent nights vs. rotating shift workers with fewer nights) might explain why more nights was associated with less anxiety. Rotating too quickly between shifts has been shown to increase anxiety (Chang et al., ) and nurses who changed from night work to day work reported a significant decrease in symptoms of both anxiety and depression (Bjorvatn, Torsheim, Moen, Magerøy, & Pallesen, ). In the current study, night shifts were undertaken in 2–4‐week blocks, possibly reducing the amount of rotation for that period and thus anxiety, but other factors may have contributed to this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A difference in shift schedules (permanent nights vs. rotating shift workers with fewer nights) might explain why more nights was associated with less anxiety. Rotating too quickly between shifts has been shown to increase anxiety (Chang et al., ) and nurses who changed from night work to day work reported a significant decrease in symptoms of both anxiety and depression (Bjorvatn, Torsheim, Moen, Magerøy, & Pallesen, ). In the current study, night shifts were undertaken in 2–4‐week blocks, possibly reducing the amount of rotation for that period and thus anxiety, but other factors may have contributed to this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep loss can affect resilience to stress, accelerating the development of cognitive consequences and the ability to utilize strategies to manage anxiety (Chang et al., ; Kalmbach et al., ). Furthermore, the more an individual is affected negatively by stress, the greater the impact on their sleep (Adriaenssens et al., ; Kalmbach et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Korompeli et al (2009) have compared the night shift workers for 9 years with the day shift workers for 17.5 years Burdelak et al (2012). andChang et al (2014) were not eligible for analysis. The two papers have assessed thyroid disorders through different variables, which are inconsistent with the other papers Burdelak et al (2012).…”
mentioning
confidence: 99%
“…[20] Another study found that nurses who worked 2 consecutive rotating 8-hour shifts had higher anxiety (stress) and poorer performance than did those who worked 4 consecutive 8-hour shifts; however, the sample size was small. [21] Chen et al [10] collected data on a very small number of nurses during 2 consecutive 12-hour shifts and reported heart rate elevations associated with increased acute fatigue with care activities such as manual patient handing versus care coordination activities. [10] In a study of nurses working 3 consecutive 12-hour days, nights, fixed, or rotating shifts, Han et al [22] reported that nurses working rotating shifts had higher levels of acute fatigue than did those on days, nights, or fixed shifts.…”
Section: Literature Reviewmentioning
confidence: 99%